2000
DOI: 10.1023/a:1009222705659
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Novel homotetranuclear Cu(II) and heteronuclear Cu(II)-Mn(II) complexes with tetrathioether-tetrathiol moiety have been prepared and their DNA relaxation activities with plasmid pCYTEXP (5kb) were electrophoretically established. The cleavage products analyzed by neutral agarose gel electrophoresis indicated that the interaction of the metal complexes with supercoiled plasmid DNA yielded linear, nicked or degraded DNA. The relaxation activities of both homo- and heterotetranuclear (SK4) complexes are time- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Dulger group has shown double-stranded DNA cleavage mediated by heterotetranuclear Cu 2+ Mn 2+ complexes based on a tetrathioether-tetrathiol ligand [91]. In the absence of external oxidants, the tetranuclear complex cleaved supercoiled DNA to yield linear DNA within 5 min at 10-50 M concentrations.…”
Section: Miscellaneous Di-and Multi-nuclear Metal Complexesmentioning
confidence: 99%
“…Dulger group has shown double-stranded DNA cleavage mediated by heterotetranuclear Cu 2+ Mn 2+ complexes based on a tetrathioether-tetrathiol ligand [91]. In the absence of external oxidants, the tetranuclear complex cleaved supercoiled DNA to yield linear DNA within 5 min at 10-50 M concentrations.…”
Section: Miscellaneous Di-and Multi-nuclear Metal Complexesmentioning
confidence: 99%
“…The mechanisms of cleavage were not determined and are presumed to be hydrolytic. Dulger et al [52] have shown ds DNA cleavage by heterotetranuclear Cu 2+ /Mn 2+ complexes based on a tetrathioether-tetrathiol ligand. In the absence of external oxidants, the tetranuclear complex cleaved supercoiled DNA to yield linear DNA within 5 min at 10±50 M concentrations.…”
Section: Double-strand Dna Cleavage By Metal Complexesmentioning
confidence: 99%
“…The pBR322 plasmid DNA cleavage activity of ZnPc-2 was also studied by agarose gel electrophoresis. 59 The supercoiled pBR322 plasmid DNA was incubated with varying concentrations of ZnPc-2 . The restriction endonuclease Eco RI was used to identify the linear form of pBR322 plasmid DNA.…”
Section: Resultsmentioning
confidence: 99%